2019
DOI: 10.1080/13506129.2019.1625323
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic degenerative thoracic aneurysms are associated with increased aortic medial amyloid

Abstract: Objective: To explore the relationship of aortic medial amyloid with biochemical and micromechanical properties of the aortic wall in aneurysm patients.Methods: Human aortic tissues removed during aneurysm surgery from tricuspid (idiopathic degenerative aneurysm, DA) and bicuspid valve (BAV) patients were subjected to oscillatory nanoindentation experiments to determine localised mechanical properties of the tissue (shear storage modulus, G´ and shear loss modulus, G˝). Collagen, elastin, matrix metalloprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…1A) or indicating an early stage of fibril formation and/or maturation. Interestingly, it has been reported that in human aortic tissue the amount of Medin in its amyloid state is significantly lower in patients with aortic aneurysm or dissection, while nonfibrillar Medin deposits are significantly higher in the diseased aorta (10) and correlate with reduced aortic elasticity (9). Thus, nonfibrillar forms of Medin could in fact be more pathogenic, and notably, we find that Medin deposits in the human brain vasculature do not stain with amyloid dyes.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…1A) or indicating an early stage of fibril formation and/or maturation. Interestingly, it has been reported that in human aortic tissue the amount of Medin in its amyloid state is significantly lower in patients with aortic aneurysm or dissection, while nonfibrillar Medin deposits are significantly higher in the diseased aorta (10) and correlate with reduced aortic elasticity (9). Thus, nonfibrillar forms of Medin could in fact be more pathogenic, and notably, we find that Medin deposits in the human brain vasculature do not stain with amyloid dyes.…”
Section: Discussionmentioning
confidence: 44%
“…Under which conditions and how Medin is cleaved from MFG-E8 remains unknown, but its exceedingly high prevalence in the aging population begs the question whether Medin-similar to other amyloids-is associated with tissue dysfunction (6). Of note, previous research suggests that ageassociated structural and functional alterations of the arteries contribute to cardiovascular diseases (7), and a role of Medin in promoting age-related vascular dysfunction has been hypothesized based on analyses of human autopsy and postmortem aorta samples (8)(9)(10). Most recently, evidence of increased Medin levels in patients with vascular dementia compared to cognitively unimpaired individuals was also reported (11).…”
mentioning
confidence: 99%
“…The influence of agitation in aggregation may have implications in the formation of medin toxic species and deposition in atherosclerosis-prone vascular regions subjected to abnormal shear stress hemodynamics, a subject requiring further empiric study. Possibly related to this, we recently found that 89% (eight out of nine) of identified oligomer-rich thoracic aortic aneurysm patients had diagnosed hypertension, compared with 54% (seven out of 13) of patients with syndromic thoracic aortic aneurysm due to bicuspid valve disorder ( 28 ). We routinely observe medin aggregation into amyloid fibers when phosphate buffers are used for medin incubation ( 23 , 78 ); however, the protofibrillar structures formed by medin aggregates ( Figs.…”
Section: Discussionmentioning
confidence: 93%
“…Medin is the main constituent of AMA, the most common form of localized amyloid ( 20 ). Little is known about its exact in vivo pathological role; however, ex vivo evidence suggests medin is implicated in multiple cardiovascular disorders ( 28 , 29 , 30 , 31 ), including vascular contributions to neurodegeneration ( 33 , 34 ) and vascular dementia ( 32 ). An in vivo study found higher abundance of nonamyloidogenic medin species in aortas from patients with either thoracic aortic aneurysms or aortic dissection than in control individuals with normal aortas ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation